2019
DOI: 10.1007/s40520-019-01395-0
|View full text |Cite
|
Sign up to set email alerts
|

Robotic balance assessment in community-dwelling older people with different grades of impairment of physical performance

Abstract: Background Impaired physical performance is common in older adults and has been identified as a major risk factor for falls. To date, there are no conclusive data on the impairment of balance parameters in older subjects with different levels of physical performance. Aims The aim of this study was to investigate the relationship between different grades of physical performance, as assessed by the Short Physical Performance Battery (SPPB), and the multidimensional balance control parameters, as measured by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In the balance tests (Exercises 2-6) the following indicators, usually computed in standard posturography [30][31][32] and already validated for hunova for elderly subjects [13], for the trunk sensor and the platform (base or seat) were considered:…”
Section: Robotic Data Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the balance tests (Exercises 2-6) the following indicators, usually computed in standard posturography [30][31][32] and already validated for hunova for elderly subjects [13], for the trunk sensor and the platform (base or seat) were considered:…”
Section: Robotic Data Processingmentioning
confidence: 99%
“…• First, we identified a minimal set of clinical parameters by using a fixed dataset of robotic variables and comparing different configurations of clinical assessments. Specifically, the subset of robotic variables was selected on the basis of the results of a previous study [13], in which we investigated the correlation between hunova parameters during standing and sitting balance tasks and the Short Physical Performance Battery test (SPPB) in communitydwelling older adults; in that study, we found the strongest correlation with trunk control parameters in standing conditions (see the selected subset in S2 Table).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…We have not found robotic rehabilitation platforms explicitly designed for HF rehabilitation. Some of the general purpose robotic platforms have been tested in HF patients for balance control exercises and monitoring [38]. However, given that they are not designed speci cally for HF rehabilitation, they are not optimized for gait speeds or sway adequate for these patients, nor they provide weight support for early post-operative mobilization [39].…”
Section: Introductionmentioning
confidence: 99%